Mechanical behavior of metal seals with the disordered entangled stainless-steel wire as core. Issue 2 (17th January 2023) - Shi, Linwei; Ren, Zhiying; Bai, Hongbai; Shen, Liangliang; Lin, Youxi; Wang, Zheng; Huang, Wei
Abstract: As a novel lightweight metallic structure, metal rubber seals (MRS) can be used for sealing elements in extreme environments where traditional polymer rubber seals become ineffective. In the present work, a virtual fabrication technology (VFT) of MRS based on computer-aided simulation technology was developed to accurately reflect the random contact interface behavior between the disordered spiral network structure of MRS core and metal sheet. The mechanical properties (meso contact characteristics and macro structural response) of the complex structure were characterized by numerical analysis and compressive tests. The effect of the compression ratio and material porosity on contact pressure performances of sealing interface was analyzed in detail. It is found that the meso contact pressure of MRS is affected by the joint action of compression condition, inner core support and cladding failure. There is a turning point in a certain range, which allow the MRS prepared in this work has the relatively best contact characteristics when the porosity is 51.5% and the compression condition is 15%. The force-displacement curves obtained from simulation and experiment both exhibit an obvious nonlinearity and slow growth area, which confirm that the MRS constitutive model based on VFT can effectively characterize the multi-scale conformity of MRS specimens from meso-structure to macro-performance.